2020
DOI: 10.3390/pharmacy8030134
|View full text |Cite
|
Sign up to set email alerts
|

A Research Partnership to Enhance Postgraduate Pharmacy Residency Training Outcomes

Abstract: Pharmacy residents must complete research as part of their program; however, challenges exist in providing experiences that result in successful research dissemination outcomes. A university-based research team, integrated into an ambulatory care pharmacy residency program aimed to improve presentation and publication rates of pharmacy resident research projects. Data on the number of postgraduate year-2 (PGY2) residents and their productivity were collected and summarized to assess progress. A total of 13 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In addition to providing a more informative representation of the PGY1 research experience itself, indicating previous or ongoing resident research efforts may give prospective candidates a richer picture of pharmacists' clinical practice at the residency site by highlighting recent patient care initiatives or clinical controversies. Articles describing programs' approaches to residency research training have been reviewed elsewhere 26 ; notably, partnering with other residency programs to establish research training networks 27 or collaborating with researchers at a local college of pharmacy 28 are strategies that have been used successfully and may be preferable for PGY1 programs with limited internal resources.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing a more informative representation of the PGY1 research experience itself, indicating previous or ongoing resident research efforts may give prospective candidates a richer picture of pharmacists' clinical practice at the residency site by highlighting recent patient care initiatives or clinical controversies. Articles describing programs' approaches to residency research training have been reviewed elsewhere 26 ; notably, partnering with other residency programs to establish research training networks 27 or collaborating with researchers at a local college of pharmacy 28 are strategies that have been used successfully and may be preferable for PGY1 programs with limited internal resources.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the use of an interprofessional, university-based research team that was developed to address challenges in the resident research process led to all residents presenting at one regional or national presentation. 42 In another study, residents given advice by an institution-specific research committee (with clinical pharmacy specialists, a data analytics expert, and a statistics expert) led over 80% of surveyed residents to agree that the committee helped anticipate barriers and improved project quality. 43 T A B L E 1 Recommendations to enhance the value of resident research and projects.…”
Section: Previous Research Experiencementioning
confidence: 99%
“…Availability of experienced collaborators is often a challenge that may be addressed by involving non‐site‐specific and non‐pharmacist research experts as needed. In one study, the use of an interprofessional, university‐based research team that was developed to address challenges in the resident research process led to all residents presenting at one regional or national presentation 42 . In another study, residents given advice by an institution‐specific research committee (with clinical pharmacy specialists, a data analytics expert, and a statistics expert) led over 80% of surveyed residents to agree that the committee helped anticipate barriers and improved project quality 43 …”
Section: Research Readinessmentioning
confidence: 99%
“…Studies have shown the value of pharmacy students, residents, and fellows conducting research. [6][7][8][9][10][11] However, when pharmacy students, residents, fellows, faculty, or other early career pharmacists do engage in research, it is often their first time, or one of their first times, and they may therefore be unprepared.…”
Section: Introductionmentioning
confidence: 99%
“…Some pharmacy students, residents, or fellows pursue a career in academia where they are typically required to engage in scholarly activities. Studies have shown the value of pharmacy students, residents, and fellows conducting research 6–11 . However, when pharmacy students, residents, fellows, faculty, or other early career pharmacists do engage in research, it is often their first time, or one of their first times, and they may therefore be unprepared.…”
Section: Introductionmentioning
confidence: 99%